The Influence of Psychological Capital and Transformational Leadership on Work Engagement of Generation Z Workers in Karawang - Ismi Noor Fajrin; Linda Mora; Haryanti Mustika (CV. Era Digital Nusantara, 2026)
The changing composition of the workforce with the arrival of Generation Z brings new dynamics, making it important to study work engagement in this generation. This study aims to examine the influence of psychological capital and transformational leadership on work engagement among Generation Z employees in Karawang. This quantitative study used a causal design with 204 respondents selected through convenience sampling techniques. Data were collected using the UWES-9, PCQ, and MLQ questionnaires, then analyzed using multiple linear regression. The results showed that psychological capital significantly influenced work engagement, while transformational leadership did not. However, both variables simultaneously had a significant effect, contributing 32.6%. Overall, psychological capital was a stronger predictor of work engagement.